2009
DOI: 10.1177/0021998309344636
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity Properties and Heat Transfer Analysis of Multi-re-entrant Auxetic Honeycomb Structures

Abstract: In this work, the static and transient conductivity properties of a novel centersymmetric honeycomb structure are evaluated using analytical and finite element (FE) models. The honeycomb structure features a unit cell geometry allowing in-plane auxetic (negative Poisson’s ratio) deformations, and geometry parameters to be used to design the honeycomb configurations for multifunctional applications. The equivalent thermal conductivity along the two principal directions of the multi-re-entrant unit cell is calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…2. These geometries include the reentrant, multi-reentrant, chiral and anti-chiral structures [5,6,7,8,9,10,11]. Different variations of the chiral and antichiral lattices like hexachiral, tetrachiral etc.…”
Section: Design Methodsmentioning
confidence: 99%
“…2. These geometries include the reentrant, multi-reentrant, chiral and anti-chiral structures [5,6,7,8,9,10,11]. Different variations of the chiral and antichiral lattices like hexachiral, tetrachiral etc.…”
Section: Design Methodsmentioning
confidence: 99%
“…2 and include reentrant, multi-reentrant, chiral and anti-chiral structures. [5][6][7][8][9][10][11] There are, again, different variations of chiral and antichiral lattices like hexachiral, tetrachiral etc.…”
Section: Designmentioning
confidence: 99%
“…These topologies mainly involve reentrant, multi-reentrant, chiral and anti-chiral structures. [5][6][7][8][9][10][11] With growing technological capabilities in fabricating structures with more complicated geometries, research on auxetics has gained further momentum. However, in spite of enormous opportunity in potentially tweaking different properties to have more freedom in availing desired behavior, attention has scarcely been given to the analysis and design of structures involving combined conventional and auxetic cores, and such rare efforts mainly involve combining them along one dimension only.…”
Section: Introductionmentioning
confidence: 99%
“…As such, several studies reported in the literature have tried to establish the correlation between these properties and the curing temperature and the degree of cure [37][38][39][40][41][42][43][44][45].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…They reported similar findings for thermal conductivity. Johnston [42] and Innocenti et al [45] described thermal conductivity of composite materials as a vector quantity which is directionally dependent. …”
Section: Thermal Propertiesmentioning
confidence: 99%